1998
DOI: 10.1002/(sici)1096-9861(19980504)394:2<242::aid-cne8>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1? and its type 1 receptor are expressed in developing neural circuits in the frog,Xenopus laevis

Abstract: The cytokine interleukin-1 beta (IL-1beta) is an evolutionarily conserved molecule that was originally identified in the immune system. In addition to regulating peripheral immune responses, IL-1beta plays an important role in mediating neural-immune interactions and regulating glial activities during healing and repair in the damaged nervous system. Active IL-1beta is produced by interleukin-converting enzyme (ICE), a caspase thought to be involved in the induction of apoptosis. We report that, in the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 79 publications
1
13
0
Order By: Relevance
“…In this report, co‐localization of NGF and IL‐1β was assessed using double‐label ICC in 10 days post‐fertilization tadpoles ( N = 5), a developmental stage that showed robust expression of both IL‐1β and NGF (Jelaso et al, 1998). Double‐label ICC experiments showed that IL‐1β was present in almost all cell types and/or regions that showed NGF‐IR (listed in Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this report, co‐localization of NGF and IL‐1β was assessed using double‐label ICC in 10 days post‐fertilization tadpoles ( N = 5), a developmental stage that showed robust expression of both IL‐1β and NGF (Jelaso et al, 1998). Double‐label ICC experiments showed that IL‐1β was present in almost all cell types and/or regions that showed NGF‐IR (listed in Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…5a). Additional cell types that expressed only IL‐1β are described in more detail in Jelaso et al (1998).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays it is known that several interleukins are expressed in normal embryonic cells at very early stages of development [28][29][30]; we have previously demonstrated that IL1b is expressed in the neuroepithelium of the embryonic spinal cord and stimulates proliferation and differentiation in these cells [31]. Moreover, receptors for IL-6 and IL-8 have been detected in numerous tissues and organs in human foetuses [32].…”
Section: Interleukin Expression and Function During Embryonic Developmentioning
confidence: 93%
“…The supernatant was collected and centrifuged at 16 000 3 g for 30 min to separate the membrane fraction. The latter was resuspended in PBS and the membranebound receptor proteins were solubilized by incubating the membrane fraction with an equal volume of 16 mM CHAPS for 30 min at 48C, followed by ultracentrifugation at 150 000 3 g for 60 min [26]. The supernatant was assayed for total protein content (Bradford; Bio-Rad) and stored at À808C until Western blot analysis.…”
Section: Extraction Of Il1r1 Membrane Proteinmentioning
confidence: 99%